SYNTHESIS AND ANTIFUNGAL ACTIVITY OF DIARYL HYDRAZONES FROM 2,4 DINITROPHENYLHYDRAZINE - Ortiz, Sergio; Nelson, Ronald; Kesternich, Víctor; Pérez-Fehrmann, Marcia; Christen, Philippe; Marcourt, Laurence (Journal of the Chilean Chemical Society, 2016)
A new series of diarylhydrazones derived from 2,4-dinitrophenylhydrazine were synthesized via condensation with aromatic aldehydes whose structures have been determined by mass spectrometry, infrared spectroscopy, and nuclear magnetic resonance spectra. Yields were 50–99%. All compounds were screened in vitro for their antifungal activity. Preliminary results indicated that compounds 3g and 3h exhibited promising antifungal potency. Understanding of the structure of these compounds establishes a preliminary structure-activity relationship to form the basis of further investigation.